(untitled) (Scientific journal of the Fergana State University, 2025)
This article delves into the historical progression of post-apocalyptic themes in literature. It explores the various stages of the genre’s growth, delves into the core themes, and examines how they have evolved over time in response to historical and cultural influences. The article showcases prominent works and authors that have shaped the genre, while also discussing the processes involved in the creation and impact of post-apocalyptic motifs. The findings underscore the significance of post-apocalyptic literature in deciphering societal shifts and its role in molding collective consciousness.